London's Arts Labs and the 60s Avant-Garde, David Curtis (2020). (1st April 2022) - Hamlyn, Nicky
Review of: London's Arts Labs and the 60s Avant-Garde, David Curtis (2020)Artists' Film, David Curtis (2021)New Barnet: John Libbey, 170 pp., ISBN 978-0-86196-748-3, p/bk, £24.99 eISBN 978-0-86196-979-1, e-book, £17.20London: Thames and Hudson, 338 pp., ISBN 978-0-50020-473-3, p/bk, £16.99